Method for improving film thickness between poly sheets of TOPcon battery

By optimizing the pretreatment steps and adopting a three-step deposition process, the problem of poor inter-sheet film thickness uniformity in the TOPCon process technology is solved, achieving more efficient silane use and battery performance improvement.

CN119630093APending Publication Date: 2025-03-14HUAIAN JIETAI NEW ENERGY TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411556439.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the TOPCon process technology, after the LP single plug production is changed to the double plug production, the uniformity of the film thickness between poly sheets may deteriorate, especially after the new boat is saturated, the thickness of the poly film may be thinner.

Method used

By optimizing the pretreatment steps, the cleaning of the quartz boat holder was eliminated, and a three-step deposition process was adopted to accurately control the thickness, composition and structure of the tunneled oxide layer and the passivation layer.

Benefits of technology

It effectively reduces silane consumption, reduces production costs, and improves the open circuit voltage and short circuit current of the battery, improving the photoelectric conversion efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119630093A_ABST
    Figure CN119630093A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of silicon solar cells, and relates to a method for improving the thickness of a film between poly sheets of a TOPcon cell, which comprises the following steps: S1, pretreating a quartz boat, S2, detecting the air tightness of a furnace tube, S3, loading the sheets, entering the boat, S4, vacuumizing, S5, carrying out constant-pressure ventilation, S6, carrying out a multi-layer deposition process, S7, vacuumizing, S8, introducing nitrogen to return pressure, and S9, taking out of the boat and unloading a silicon wafer. According to the invention, the problem that the uniformity of the film thickness between poly sheets becomes poor when LP single-insertion production is changed into double-insertion process production is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of silicon solar cells and relates to a method for improving the film thickness between poly sheets of a TOPcon cell. Background Art

[0002] TOPCon process technology, full name Tunneling Oxide Passivation Contact Technology, is an advanced process technology with significant advantages in the field of photovoltaic cell manufacturing. Its core concept is to effectively reduce the recombination of conjugated pairs by separating hole-electron conjugated pairs, thereby greatly improving the power generation performance of photovoltaic cells. The realization of this technology is based on the principle of selective carriers. By carefully preparing an ultra-thin layer of silicon oxide on the back of the cell and depositing a thin layer of doped silicon on it, the two together constitute an efficient passivation contact structure.

[0003] The passivation contact structure plays a vital role in photovoltaic cells. It can not only significantly reduce the recombination rate on the cell surface, but also effectively reduce metal contact recombination, opening up a broad space for further improving the cell conversion efficiency. Therefore, once the TOPCon process technology was launched, it was quickly widely used in the field of photovoltaic cell manufacturing and became one of the current mainstream photovoltaic cell technologies.

[0004] With the continuous development and improvement of TOPCon process technology, its core process LPCVD (low pressure chemical vapor deposition) has also made significant progress. In order to meet higher output requirements, the LPCVD process has been deeply developed, evolving from the original single-insert process to a double-insert process. This change means that in the original quartz boat, the original 1 slot 1 piece has been changed to 1 slot 2 pieces, which greatly improves production capacity.

[0005] However, the change from LP single-insert production to double-insert process production also brings some challenges. In particular, under the double-insert process, the uniformity of film thickness between poly sheets may deteriorate. This problem is particularly prominent after the Xinzhou is saturated and put into production, because it may take some time for Xinzhou to reach the optimal saturation state during use, and during this period, the thickness of the poly film may be thin. Therefore, how to ensure the uniformity of film thickness between poly sheets while ensuring capacity increase has become one of the key challenges for the further development of TOPCon process technology. Summary of the invention

[0006] The purpose of the present invention is to provide a method for improving the film thickness between poly sheets of TOPcon cells, so as to solve the problem that the uniformity of the film thickness between poly sheets will deteriorate when the LP single-insertion production is changed to the double-insertion process production.

[0007] The technical solution adopted by the present invention is a method for improving the film thickness between poly sheets of TOPcon cells, comprising the following steps:

[0008] Step 1, pre-treating the quartz boat, the object of pre-treatment does not include the quartz boat support;

[0009] Step 2, testing the air tightness of the furnace tube;

[0010] Step 3, loading wafers and boats, loading silicon wafers into quartz boats, transporting the quartz boats into furnace tubes, heating the furnace tubes and keeping the temperature constant at 600-700°C for 500-700s, and simultaneously purging with nitrogen for 3-5min;

[0011] Step 4, evacuate the furnace tube treated in step 3, evacuate to bottom pressure for 2 to 3 minutes, and keep the temperature constant at 550 to 600°C;

[0012] Step 5, constant pressure ventilation, pre-introducing a certain amount of silane into the furnace tube treated in step 4, so that the furnace tube pressure rises and maintains a constant pressure, and the temperature is constant at 550-600° C.;

[0013] Step 6, multi-layer deposition process, the first high-temperature silane is introduced, the silane is thermally decomposed into a first layer of silicon single substance deposited on the surface of the passivation layer; the second high-temperature silane is introduced, the silane is thermally decomposed into a second layer of silicon single substance deposited on the surface of the passivation layer; the third high-temperature silane is introduced, the silane is thermally decomposed into a third layer of silicon single substance deposited on the surface of the passivation layer;

[0014] Step 7: After the multi-layer deposition process is completed, the unreacted gas and some products are pumped out of the furnace tube through a vacuum pump;

[0015] Step 8: Back pressure: fill the furnace tube with nitrogen to return the pressure to normal pressure, ready for boat unloading;

[0016] Step 9: Unload the silicon wafers from the boat, take them out of the quartz boat, insert them into the basket, and transfer them to the next process.

[0017] The present invention is also characterized in that:

[0018] Further, the preprocessing comprises the following steps:

[0019] The quartz boat is treated with alkaline solution;

[0020] The quartz boat after alkali washing is subjected to water washing;

[0021] The quartz boat is pickled with a mixed acid solution;

[0022] The quartz boat after pickling is washed with water;

[0023] The quartz boat after water washing is slowly pulled and dehydrated;

[0024] The dehydrated quartz boat is dried.

[0025] Furthermore, the alkaline solution is a mixed solution of NaOH and H2O2, wherein the volume fraction of NaOH in the mixed solution is 2.5-4.0%, and the volume fraction of H2O2 in the mixed solution is 3.5-6.0.

[0026] Furthermore, the mixed acid solution comprises the following components by mass percentage: 0.3-1.5% hydrogen chloride, 0.1-0.2% hydrogen fluoride, 0.05-0.4% oxidant, 0.05-0.1% complexing agent, 0.02-0.05% surfactant, and the balance is water.

[0027] Further, the oxidant is selected from any one of hydrogen peroxide, peracetic acid or ammonium persulfate, or a combination of at least two thereof;

[0028] The complexing agent is any one of ethylenediaminetetraacetic acid, hydroxyethyliminodiacetic acid, and hydroxyethylethylenediaminetriacetic acid, or a combination of at least two thereof;

[0029] The surfactant is any one of palmitoleic acid, polyethylene glycol or fatty alcohol polyoxyethylene ether, or a combination of at least two of them.

[0030] Furthermore, it is characterized in that the alkali washing treatment is carried out according to the following steps:

[0031] Firstly, the quartz boat is placed in the alkaline solution for soaking, and then ultrasonically rinsed;

[0032] The temperature of the static soaking is 15-35°C, and the time of the static soaking is 30-50 minutes;

[0033] The temperature of ultrasonic rinsing is 30-40°C, the frequency of ultrasonic rinsing is 30-40kHz, and the time of ultrasonic rinsing is 45-60min;

[0034] The pickling treatment is carried out according to the following steps:

[0035] Firstly, the quartz boat is placed in the mixed acid solution for static soaking, and then ultrasonically rinsed;

[0036] The temperature of the static soaking is 15-35°C, and the time of the static soaking is 30-50 minutes;

[0037] The temperature of ultrasonic rinsing is 30-40°C, the frequency of ultrasonic rinsing is 30-40kHz, and the time of ultrasonic rinsing is 45-60min;

[0038] The specific steps of the water washing treatment are:

[0039] First, place the quartz boat after acid or alkali washing in pure water for static soaking, and then spray rinse;

[0040] The temperature of the static soaking is 10-20°C, and the time of the static soaking is 20-40 minutes;

[0041] The temperature of the spray rinsing is 10-20°C, and the flow rate of the spray rinsing is 5-15m 3 / h, the spray rinsing time is 30 to 60 minutes.

[0042] Furthermore, the constant pressure in step 5 is maintained at 150 mbar.

[0043] Furthermore, the vacuuming conditions in step 7 are set to a temperature of 550-600° C. and a time of 1-3 minutes.

[0044] Furthermore, the back pressure conditions of step 8 are set as a temperature of 550-600° C., a nitrogen flow rate of 10000-30000 sccm, and a time of 1-3 min.

[0045] Furthermore, the parameters of the first deposition in step 6 are set as follows: the temperature is set at 500-650° C., the silane flow rate is 200-650 sccm, and the time is 45-60 min;

[0046] The parameters of the second deposition are set as temperature at 500-650° C., silane flow rate at 200-650 sccm, and time at 30-45 min.

[0047] The parameters of the third deposition are set as follows: temperature is set at 500-650° C., silane flow rate is 200-650 sccm, and time is 35-40 min.

[0048] The beneficial effects of the present invention are:

[0049] 1. The present invention optimizes the pretreatment steps, and the object of pretreatment does not include the quartz boat support, because the quartz boat support will absorb part of the silane deposition surface, resulting in the amount of silane required for saturated cleaning of the boat support and the boat being much greater than the saturated amount for washing only the boat. Not washing the boat support can effectively reduce the silane consumption and reduce the production cost.

[0050] 2. The present invention changes the traditional two-step deposition process into a three-step deposition process, which can more accurately control the thickness, composition and structure of the tunneling oxide layer and the passivation layer, improve the open circuit voltage and short circuit current of the battery, and thus improve the photoelectric conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0052] Figure 1 It is a schematic diagram of the process of the present invention. DETAILED DESCRIPTION

[0053] The following will be combined with the accompanying drawings in the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.

[0054] The following is combined with Figure 1 And specific embodiments, the present invention is described in detail:

[0055] A method for improving the inter-sheet film thickness of a TOPCON cell poly comprises the following steps:

[0056] Step 1: pre-treat the quartz boat. The pre-treatment object does not include the quartz boat support, because the quartz boat support will absorb part of the silane deposition surface, so the amount of silane required for saturated cleaning of the boat support and the small boat is much greater than the saturated amount for washing only the small boat. Not washing the boat support can effectively reduce the silane consumption and effectively improve the problem of thin film thickness of the first boat on the new boat line.

[0057] Step 2: The reaction needs to be completed under vacuum conditions. The air tightness of the furnace tube is tested to ensure that the leakage rate meets the process requirements and prevent air from entering.

[0058] Step 3, loading wafers and putting them into boats. Load silicon wafers into quartz boats, transport the quartz boats into furnace tubes, heat the furnace tubes and keep the temperature constant at 600-700°C for 500-700s. At the same time, introduce nitrogen for purging for 3-5min. Nitrogen takes away air and moisture in the cavity to prevent air or moisture from contaminating silicon wafers and causing dirt on the plating.

[0059] Step 4, evacuate the furnace tube treated in step 3, evacuate to the bottom pressure for 2 to 3 minutes, and achieve the vacuum conditions required for the thin film deposition reaction, and keep the temperature constant at 550 to 600° C.;

[0060] Step 5, constant pressure ventilation, before depositing the film, a certain amount of silane is pre-introduced into the furnace tube treated in step 4, so that the furnace tube reaches the pressure atmosphere required by the process in advance, the furnace tube pressure rises and maintains constant pressure, and the temperature is constant at 550-600° C. under constant pressure conditions;

[0061] Step 6, multi-layer process deposition, the first high-temperature silane is introduced, the silane is thermally decomposed into a first layer of silicon single substance deposited on the surface of the passivation layer; then the silane is introduced at high temperature for the second time, the silane is thermally decomposed into a second layer of silicon single substance deposited on the surface of the passivation layer; the third high-temperature silane is introduced, the silane is thermally decomposed into a third layer of silicon single substance deposited on the surface of the passivation layer;

[0062] The parameters of the first deposition in step 6 are set as temperature at 500-650° C., silane flow rate at 200-650 sccm, and time at 45-60 min.

[0063] The parameters of the second deposition are set as temperature at 500-650° C., silane flow rate at 200-650 sccm, and time at 30-45 min.

[0064] The parameters of the third deposition are set as follows: temperature is set at 500-650° C., silane flow rate is 200-650 sccm, and time is 35-40 min.

[0065] Step 7: After the multi-layer deposition process is completed, the unreacted gas and some products are pumped out of the furnace tube through a vacuum pump. The vacuum pumping conditions in step 7 are set at a temperature of 550-600° C. and a time of 1-3 minutes.

[0066] Step 8, back pressure, fill nitrogen into the furnace tube to return the pressure to normal pressure, ready for opening the furnace door, the back pressure conditions of step 8 are set to a temperature of 550-600°C, a nitrogen flow rate of 10000-30000sccm, and a time of 1-3min.

[0067] Step 9: Unload the silicon wafers from the boat, take them out of the quartz boat, insert them into the basket, and transfer them to the next process.

[0068] The preprocessing includes the following steps:

[0069] The quartz boat is treated with alkaline solution;

[0070] The quartz boat after alkali washing is subjected to water washing;

[0071] The quartz boat is pickled with a mixed acid solution;

[0072] The quartz boat after pickling is washed with water;

[0073] The quartz boat after water washing is slowly pulled and dehydrated;

[0074] The dehydrated quartz boat is dried.

[0075] The alkaline solution is a mixed solution of NaOH and H2O2, wherein NaOH accounts for 2.5-4.0% by volume of the mixed solution, and H2O2 accounts for 3.5-6.0% by volume of the mixed solution. In the mixed solution, NaOH can effectively decompose and remove grease, organic matter and other pollutants on the surface of the quartz boat, and H2O2 can further oxidize and decompose the pollutants on the surface of the quartz boat, thereby improving the cleaning effect.

[0076] The alkaline solution can ensure the cleaning effect while avoiding excessive corrosion and damage to the quartz boat. The surface finish of the cleaned quartz boat is higher, which helps to improve its performance and life during use. The cleaning effect of the mixed solution of NaOH and hydrogen peroxide can ensure that the surface finish of the quartz boat meets the requirements.

[0077] The mixed acid solution comprises the following components by mass percentage: 0.3-1.5% of hydrogen chloride, 0.1-0.2% of hydrogen fluoride, 0.05-0.4% of oxidant, 0.05-0.1% of complexing agent, 0.02-0.05% of surfactant, and the balance is water.

[0078] The oxidant in the mixed acid solution can further oxidize and decompose organic matter and other difficult-to-remove contaminants on the surface of the quartz boat. By enhancing the cleaning effect, the oxidant helps reduce mechanical friction and damage to the quartz boat.

[0079] The complexing agent can form a stable complex with the metal ions, thereby reducing the residual metal ions on the surface of the quartz boat. This helps prevent the metal ions from contaminating and corroding the quartz boat.

[0080] Surfactants can reduce the surface tension of the cleaning liquid, making it easier for it to penetrate into the tiny gaps and depressions on the surface of the quartz boat. This helps to improve the cleaning effect and reduce damage to the quartz boat during the cleaning process.

[0081] The various components in the mixed acid solution can work synergistically at appropriate concentrations, improving the cleaning effect while reducing environmental pollution. This helps reduce the wastewater treatment costs and negative impacts on the environment during the cleaning process.

[0082] The oxidant is selected from any one of hydrogen peroxide, peracetic acid or ammonium persulfate or a combination of at least two of them. The above oxidants all have strong oxidizing properties and can effectively remove pollutants such as organic matter and metal impurities on the surface of the quartz boat. Among them, hydrogen peroxide and peracetic acid will release new ecological oxygen when encountering organic matter, play an oxidizing role, and oxidize and decompose the pollutants; ammonium persulfate also has strong oxidizing properties and can quickly decompose to produce sulfate ions and free radicals, which further react with the pollutants.

[0083] The combined use of these oxidants can work synergistically with each other to improve cleaning efficiency. Different oxidants may have different removal effects on different types of contaminants, so the combined use can ensure a more comprehensive removal of contaminants on the surface of the quartz boat.

[0084] The above-mentioned oxidants usually only produce oxygen, water or other harmless substances after decomposition, so no harmful residues are left after use. This is crucial for the manufacturing process of TOPCON batteries, because any harmful residues may affect the performance and efficiency of the battery.

[0085] The complexing agent is any one of ethylenediaminetetraacetic acid, hydroxyethyliminodiacetic acid, and hydroxyethylethylenediaminetriacetic acid, or a combination of at least two thereof.

[0086] Using any one of ethylenediaminetetraacetic acid (EDTA), hydroxyethyliminodiacetic acid or hydroxyethylethylenediaminetriacetic acid or a combination of at least two as a complexing agent to clean the quartz boat used by TOPCON can bring the following beneficial effects:

[0087] The above-mentioned complexing agent can form a stable complex with metal ions (such as iron, copper, nickel, etc.) on the surface of the quartz boat, thereby effectively removing these metal ions. This complexing action can prevent the metal ions from depositing on the surface of the quartz boat and avoid interference with subsequent processes.

[0088] Through the complexation of the complexing agent with the metal ions, the metal ions on the surface of the quartz boat can be quickly removed, improving the cleaning efficiency. This is crucial for the manufacturing process of TOPCON batteries, because the presence of metal ions may affect the performance and efficiency of the battery.

[0089] Compared with traditional mechanical cleaning methods, cleaning with complexing agents can reduce mechanical damage to the surface of the quartz boat. The complexing agent can penetrate into the tiny gaps and depressions on the surface of the quartz boat, form complexes with metal ions and remove them without damaging the surface structure of the quartz boat. By removing metal ions and other contaminants on the surface of the quartz boat, the performance of the quartz boat can be kept stable. This is crucial to ensure the quality and reliability of TOPCON cells.

[0090] The complexing agent forms a stable complex with the metal ions during the cleaning process, thereby reducing the toxicity of the cleaning wastewater. This helps reduce the cost and environmental risks during the wastewater treatment process. Compared with wastewater containing heavy metal ions, wastewater containing complexes is easier to handle and dispose of. This helps reduce wastewater treatment costs and reduces pollution to the environment.

[0091] The surfactant is any one of palmitic acid, polyethylene glycol or fatty alcohol polyoxyethylene ether or a combination of at least two thereof.

[0092] Surfactants can significantly reduce the surface tension of water, allowing water to better penetrate into the tiny gaps and depressions on the surface of the quartz boat, thereby more effectively removing surface dirt and pollutants. Surfactants penetrate into the dirt on the surface of the quartz boat and remove it through chemical reactions or physical actions without damaging the surface structure of the quartz boat.

[0093] By removing dirt and contaminants from the surface of the quartz boat, its surface smoothness and cleanliness can be maintained, thus ensuring its stable performance. This is crucial to the manufacturing process of TOPCON cells, as the performance of the quartz boat directly affects the quality and efficiency of the cell.

[0094] Alkaline washing treatment is carried out according to the following steps:

[0095] Firstly, the quartz boat is placed in the alkaline solution for soaking, and then ultrasonically rinsed;

[0096] The temperature of the static soaking is 15-35°C, and the time of the static soaking is 30-50 minutes;

[0097] The temperature of ultrasonic rinsing is 30-40° C., the frequency of ultrasonic rinsing is 30-40 kHz, and the time of ultrasonic rinsing is 45-60 min.

[0098] The surface of the quartz boat after alkaline washing is cleaner and smoother, which provides a good foundation for the subsequent battery manufacturing process. A clean quartz boat can ensure process stability and product quality during battery manufacturing, thereby improving the conversion efficiency and life of the battery.

[0099] The pickling treatment is carried out according to the following steps:

[0100] Firstly, the quartz boat is placed in the mixed acid solution for static soaking, and then ultrasonically rinsed;

[0101] The temperature of the static soaking is 15-35°C, and the time of the static soaking is 30-50 minutes;

[0102] The temperature of ultrasonic rinsing is 30-40° C., the frequency of ultrasonic rinsing is 30-40 kHz, and the time of ultrasonic rinsing is 45-60 min.

[0103] Acid pickling can effectively remove oxides, nitrides or other impurities, including removing silicon oxide and silicon nitride films on the surface of silicon wafers, ensuring the cleanliness of the silicon wafer surface and providing high-quality silicon wafers for subsequent process steps.

[0104] The specific steps of water washing treatment are:

[0105] First, place the quartz boat after acid or alkali washing in pure water for static soaking, and then spray rinse;

[0106] The temperature of the static soaking is 10-20°C, and the time of the static soaking is 20-40 minutes;

[0107] The temperature of the spray rinsing is 10-20°C, and the flow rate of the spray rinsing is 5-15m 3 / h, the spray rinsing time is 30 to 60 minutes.

[0108] The main purpose of water washing is to remove the residual mixed acid solution or alkaline solution on the surface of the silicon wafer, as well as other impurities that may exist on the surface of the quartz boat.

[0109] In the pretreatment, alkali cleaning, acid cleaning and water washing can also be performed by tank cleaning operation. Tank cleaning can process multiple quartz boats at the same time, greatly improving the cleaning efficiency.

[0110] Example 1

[0111] Step 1, pre-treating the quartz boat, using an alkaline solution to perform alkaline washing on the quartz boat, firstly soaking the quartz boat in the alkaline solution, and then performing ultrasonic rinsing;

[0112] The temperature of static soaking is 35℃, and the time of static soaking is 50min;

[0113] The temperature of ultrasonic rinsing is 40°C, the frequency of ultrasonic rinsing is 40kHz, and the time of ultrasonic rinsing is 60min.

[0114] In the alkaline solution, NaOH accounts for 2.8% of the volume fraction of the mixed solution, and H2O2 accounts for 5.0% of the volume fraction of the mixed solution.

[0115] The quartz boat after the alkali washing is subjected to water washing, firstly the quartz boat after the alkali washing is soaked in pure water, and then sprayed and rinsed;

[0116] The temperature of static soaking is 20℃, and the time of static soaking is 35min;

[0117] The temperature of the spray rinsing is 105°C and the flow rate of the spray rinsing is 14m 3 / h, the spray rinsing time is 30min.

[0118] The quartz boat is pickled with a mixed acid solution, the quartz boat is firstly soaked in the mixed acid solution, and then ultrasonically rinsed;

[0119] The temperature of static soaking is 35℃, and the time of static soaking is 50min;

[0120] The temperature of ultrasonic rinsing is 40°C, the frequency of ultrasonic rinsing is 40kHz, and the time of ultrasonic rinsing is 60min.

[0121] The mixed acid solution is composed of 0.3% hydrogen chloride, 0.1% hydrogen fluoride, 0.05% oxidant, 0.05% complexing agent, 0.05% surfactant, and the balance is water. The oxidant is a combination of hydrogen peroxide and ammonium persulfate; the complexing agent is ethylenediaminetetraacetic acid; and the surfactant is a combination of polyethylene glycol and fatty alcohol polyoxyethylene ether.

[0122] The quartz boat after pickling is washed with water, firstly, the quartz boat after pickling is soaked in pure water, and then sprayed and rinsed;

[0123] The temperature of static soaking is 14℃, and the time of static soaking is 30min;

[0124] The temperature of the spray rinse is 18°C ​​and the flow rate of the spray rinse is 10m 3 / h, the spray rinsing time is 40min.

[0125] The quartz boat after water washing is slowly pulled and dehydrated;

[0126] The dehydrated quartz boat is dried.

[0127] Step 2, testing the air tightness of the furnace tube;

[0128] Step 3, loading the film and placing it in the boat, raising the temperature in the furnace tube and keeping it constant at 600°C for 500s, while nitrogen gas is introduced for purging for 3min;

[0129] Step 4: Vacuum, evacuate to bottom pressure for 2 minutes, and keep the temperature constant at 550°C;

[0130] Step 5: Constant pressure ventilation, the furnace tube pressure rises and remains constant at 550°C;

[0131] Step 6: introduce silane at high temperature for the first time, with the temperature set at 500°C, the silane flow rate at 200sccm, and the time being 45min; then introduce silane at high temperature for the second time, with the temperature set at 500°C, the silane flow rate at 200sccm, and the time being 30min; finally, introduce silane at high temperature for the third time, with the temperature set at 500°C, the silane flow rate at 200sccm, and the time being 35min.

[0132] After step 7 and step 6, vacuum is applied, and the vacuuming condition is set at a temperature of 550°C and a time of 1 minute;

[0133] Step 8: back pressure. The back pressure conditions are set as a temperature of 550-600° C., a nitrogen flow rate of 10,000 sccm, and a time of 1 min.

[0134] Step 9: Unload the silicon wafers from the boat, take them out of the quartz boat, insert them into the basket, and transfer them to the next process.

[0135] In order to verify the beneficial effects of the present invention, the product of Example 1 was selected for a control group experiment.

[0136] The control group experiment was carried out according to the following steps:

[0137] Step 1, pre-treating the quartz boat and the boat support, using an alkaline solution to perform alkaline cleaning on the quartz boat, firstly soaking the quartz boat in the alkaline solution, and then performing ultrasonic rinsing;

[0138] The temperature of static soaking is 35℃, and the time of static soaking is 50min;

[0139] The temperature of ultrasonic rinsing is 40°C, the frequency of ultrasonic rinsing is 40kHz, and the time of ultrasonic rinsing is 60min.

[0140] In the alkaline solution, NaOH accounts for 2.8% of the volume fraction of the mixed solution, and H2O2 accounts for 5.0% of the volume fraction of the mixed solution.

[0141] The quartz boat after the alkali washing is subjected to water washing, firstly the quartz boat after the alkali washing is soaked in pure water, and then sprayed and rinsed;

[0142] The temperature of static soaking is 20℃, and the time of static soaking is 35min;

[0143] The temperature of the spray rinsing is 105°C and the flow rate of the spray rinsing is 14m 3 / h, the spray rinsing time is 30min.

[0144] The quartz boat is pickled with a mixed acid solution, the quartz boat is firstly soaked in the mixed acid solution, and then ultrasonically rinsed;

[0145] The temperature of static soaking is 35℃, and the time of static soaking is 50min;

[0146] The temperature of ultrasonic rinsing is 40°C, the frequency of ultrasonic rinsing is 40kHz, and the time of ultrasonic rinsing is 60min.

[0147] The mixed acid solution is composed of 0.3% hydrogen chloride, 0.1% hydrogen fluoride, 0.05% oxidant, 0.05% complexing agent, 0.05% surfactant, and the balance is water. The oxidant is a combination of hydrogen peroxide and ammonium persulfate; the complexing agent is ethylenediaminetetraacetic acid; and the surfactant is a combination of polyethylene glycol and fatty alcohol polyoxyethylene ether.

[0148] The quartz boat after pickling is washed with water, firstly, the quartz boat after pickling is soaked in pure water, and then sprayed and rinsed;

[0149] The temperature of static soaking is 14℃, and the time of static soaking is 30min;

[0150] The temperature of the spray rinse is 18°C ​​and the flow rate of the spray rinse is 10m 3 / h, the spray rinsing time is 40min.

[0151] The quartz boat after water washing is slowly pulled and dehydrated;

[0152] The dehydrated quartz boat is dried.

[0153] Step 2, testing the air tightness of the furnace tube;

[0154] Step 3, loading the film and placing it in the boat, raising the temperature in the furnace tube and keeping it constant at 600°C for 500s, while nitrogen gas is introduced for purging for 3min;

[0155] Step 4: Vacuum, evacuate to bottom pressure for 2 minutes, and keep the temperature constant at 550°C;

[0156] Step 5: Constant pressure ventilation, the furnace tube pressure rises and remains constant at 550°C;

[0157] Step 6: introduce silane at high temperature for the first time, with the temperature set at 500°C, the silane flow rate at 200sccm, and the time being 45min; then introduce silane at high temperature for the second time, with the temperature set at 500°C, the silane flow rate at 200sccm, and the time being 30min; finally, introduce silane at high temperature for the third time, with the temperature set at 500°C, the silane flow rate at 200sccm, and the time being 35min.

[0158] After step 7 and step 6, vacuum is applied, and the vacuuming condition is set at a temperature of 550°C and a time of 1 minute;

[0159] Step 8: back pressure. The back pressure conditions are set as a temperature of 550-600° C., a nitrogen flow rate of 10,000 sccm, and a time of 1 min.

[0160] Step 9: Unload the silicon wafers from the boat, take them out of the quartz boat, insert them into the basket, and transfer them to the next process.

[0161] Sample collection method: Parameter analysis is performed on the battery cells sintered in the same furnace in a boat holder. First, the 10 quartz boats in the same boat holder are numbered from 1 to 10, and then the quartz boats are divided into three areas: upper, middle and lower. Battery cells are selected from quartz boats 1, 3, 5, 7 and 9. Specifically, one battery cell is selected from each of the upper, middle and lower areas of each quartz boat, and the poly film thickness data of the central area, upper left corner area, upper right corner area, lower left corner area and lower right corner area of ​​the selected samples are measured.

[0162] Table 1 Control experiment data

[0163]

[0164]

[0165] The purpose of the first group of experiments is to verify the effect of cleaning the boat support and not cleaning the boat support on the film thickness between poly sheets. From Table 1, it can be seen that the film thickness compliance rate of the experimental group is 100%, while the film thickness compliance rate of the control group is 61%. Obviously, the film thickness compliance rate of the experimental group is much higher than that of the control group. Therefore, it can be concluded that not washing the boat support effectively improves the problem of thin poly film thickness.

[0166] Example 2

[0167] Step 1, pre-treating the quartz boat, using an alkaline solution to perform alkaline washing on the quartz boat, firstly soaking the quartz boat in the alkaline solution, and then performing ultrasonic rinsing;

[0168] The temperature of static soaking is 15℃, and the time of static soaking is 30min;

[0169] The temperature of ultrasonic rinsing is 30°C, the frequency of ultrasonic rinsing is 30kHz, and the time of ultrasonic rinsing is 45min.

[0170] In the alkaline solution, NaOH accounts for 2.5% of the volume fraction of the mixed solution, and H2O2 accounts for 6.0% of the volume fraction of the mixed solution.

[0171] The quartz boat after the alkali washing is subjected to water washing, firstly the quartz boat after the alkali washing is soaked in pure water, and then sprayed and rinsed;

[0172] The temperature of static soaking is 13℃, and the time of static soaking is 26min;

[0173] The temperature of the spray rinse is 12°C and the flow rate of the spray rinse is 8m 3 / h, the spray rinsing time is 30min.

[0174] The quartz boat is pickled with a mixed acid solution, the quartz boat is firstly soaked in the mixed acid solution, and then ultrasonically rinsed;

[0175] The temperature of static soaking is 15℃, and the time of static soaking is 45min;

[0176] The temperature of ultrasonic rinsing was 32° C., the frequency of ultrasonic rinsing was 34 kHz, and the time of ultrasonic rinsing was 46 min.

[0177] The mixed acid solution is composed of 1% hydrogen chloride, 0.15% hydrogen fluoride, 0.2% oxidant, 0.07% complexing agent, 0.03% surfactant, and the balance is water. The oxidant is hydrogen peroxide; the complexing agent is hydroxyethylethylenediaminetriacetic acid; and the surfactant is polyethylene glycol.

[0178] The quartz boat after pickling is washed with water, firstly, the quartz boat after pickling is soaked in pure water, and then sprayed and rinsed;

[0179] The temperature of static soaking is 19℃, and the time of static soaking is 26min;

[0180] The temperature of the spray rinse is 17°C and the flow rate of the spray rinse is 13m 3 / h, the spray rinsing time is 35min.

[0181] The quartz boat after water washing is slowly pulled and dehydrated;

[0182] The dehydrated quartz boat is dried.

[0183] Step 2, testing the air tightness of the furnace tube;

[0184] Step 3, loading the film and placing it in the boat, raising the temperature in the furnace tube and keeping it constant at 700°C for 700s, while nitrogen gas is introduced for 5min;

[0185] Step 4: Vacuum, evacuate to bottom pressure for 2 minutes, and keep the temperature constant at 550°C;

[0186] Step 5: Constant pressure ventilation, the furnace tube pressure rises and remains constant at 550°C;

[0187] Step 6: The first high-temperature silane is introduced at 610°C, a silane flow rate of 450 sccm, and a time of 47 min; the second high-temperature silane is introduced at 620°C, a silane flow rate of 550 sccm, and a time of 42 min; and the third high-temperature silane is introduced at 630°C, a silane flow rate of 350 sccm, and a time of 39 min.

[0188] After step 7 and step 6, vacuum is applied, and the vacuum application condition is set at a temperature of 574°C and a time of 1 to 3 minutes;

[0189] Step 8: back pressure. The back pressure conditions are set as temperature at 568° C., nitrogen flow rate at 20,000 sccm, and time at 2 min.

[0190] Step 9: Unload the silicon wafers from the boat, take them out of the quartz boat, insert them into the basket, and transfer them to the next process.

[0191] Example 3

[0192] Step 1, pre-treating the quartz boat, using an alkaline solution to perform alkaline washing on the quartz boat, firstly soaking the quartz boat in the alkaline solution, and then performing ultrasonic rinsing;

[0193] The temperature of static soaking is 18℃, and the time of static soaking is 36min;

[0194] The temperature of ultrasonic rinsing was 33°C, the frequency of ultrasonic rinsing was 32kHz, and the time of ultrasonic rinsing was 47min.

[0195] In the alkaline solution, NaOH accounts for 4.0% by volume of the mixed solution, and H2O2 accounts for 3.5% by volume of the mixed solution.

[0196] The quartz boat after the alkali washing is subjected to water washing, firstly the quartz boat after the alkali washing is soaked in pure water, and then sprayed and rinsed;

[0197] The temperature of static soaking is 11℃, and the time of static soaking is 24min;

[0198] The temperature of the spray rinse is 13°C and the flow rate of the spray rinse is 7m 3 / h, the spray rinsing time is 42min.

[0199] The quartz boat is pickled with a mixed acid solution, the quartz boat is firstly soaked in the mixed acid solution, and then ultrasonically rinsed;

[0200] The temperature of static soaking is 18℃, and the time of static soaking is 41min;

[0201] The temperature of ultrasonic rinsing was 34°C, the frequency of ultrasonic rinsing was 38 kHz, and the time of ultrasonic rinsing was 47 min.

[0202] The mixed acid solution is composed of 0.8% hydrogen chloride, 0.18% hydrogen fluoride, 0.22% oxidant, 0.06% complexing agent, 0.04% surfactant, and the balance is water. The oxidant is a combination of peracetic acid and ammonium persulfate; the complexing agent is a combination of ethylenediaminetetraacetic acid and hydroxyethylethylenediaminetriacetic acid; and the surfactant is a combination of palmitoleic acid, polyethylene glycol, and fatty alcohol polyoxyethylene ether.

[0203] The quartz boat after pickling is washed with water, firstly, the quartz boat after pickling is soaked in pure water, and then sprayed and rinsed;

[0204] The temperature of static soaking is 12℃, and the time of static soaking is 28min;

[0205] The temperature of the spray rinse is 13°C and the flow rate of the spray rinse is 7m 3 / h, the spray rinsing time is 44min.

[0206] The quartz boat after water washing is slowly pulled and dehydrated.

[0207] The dehydrated quartz boat is dried.

[0208] Step 2, testing the air tightness of the furnace tube;

[0209] Step 3, loading the film and placing it in the boat, raising the temperature in the furnace tube and keeping the temperature constant at 687°C for 634 seconds, and simultaneously introducing nitrogen to purge for 3 minutes;

[0210] Step 4: Vacuum, evacuate to bottom pressure for 2 minutes, and keep the temperature constant at 564°C;

[0211] Step 5: Constant pressure ventilation, the furnace tube pressure rises and remains constant at 577°C;

[0212] Step 6: The first high-temperature silane is introduced at 545°C, a silane flow rate of 330 sccm, and a time of 56 min; the second high-temperature silane is introduced at 570°C, a silane flow rate of 270 sccm, and a time of 33 min; and the third high-temperature silane is introduced at 550°C, a silane flow rate of 550 sccm, and a time of 36 min.

[0213] After step 7 and step 6, vacuum is applied, and the vacuuming condition is set at a temperature of 580°C and a time of 1 to 3 minutes;

[0214] Step 8: back pressure. The back pressure conditions are set as temperature at 580° C., nitrogen flow rate at 20,000 sccm, and time at 2.5 min.

[0215] Step 9: Unload the silicon wafers from the boat, take them out of the quartz boat, insert them into the basket, and transfer them to the next process.

[0216] Example 4

[0217] Step 1, pre-treating the quartz boat, using an alkaline solution to perform alkaline washing on the quartz boat, firstly soaking the quartz boat in the alkaline solution, and then performing ultrasonic rinsing;

[0218] The temperature of static soaking is 28℃, and the time of static soaking is 40min;

[0219] The temperature of ultrasonic rinsing was 36°C, the frequency of ultrasonic rinsing was 37 kHz, and the time of ultrasonic rinsing was 55 min.

[0220] In the alkaline solution, NaOH accounts for 3% of the volume fraction of the mixed solution, and H2O2 accounts for 3.6% of the volume fraction of the mixed solution.

[0221] The quartz boat after the alkali washing is subjected to water washing, firstly the quartz boat after the alkali washing is soaked in pure water, and then sprayed and rinsed;

[0222] The temperature of static soaking is 10℃, and the time of static soaking is 20min;

[0223] The temperature of the spray rinse is 10°C and the flow rate of the spray rinse is 5m 3 / h, the spray rinsing time is 30min.

[0224] The quartz boat is pickled with a mixed acid solution, the quartz boat is firstly soaked in the mixed acid solution, and then ultrasonically rinsed;

[0225] The temperature of static soaking is 15℃, and the time of static soaking is 30min;

[0226] The temperature of ultrasonic rinsing is 30°C, the frequency of ultrasonic rinsing is 30kHz, and the time of ultrasonic rinsing is 45min.

[0227] The mixed acid solution is composed of 1.1% hydrogen chloride, 0.14% hydrogen fluoride, 0.09% oxidant, 0.08% complexing agent, 0.03% surfactant, and the balance is water. The oxidant is ammonium persulfate; the complexing agent is a combination of ethylenediaminetetraacetic acid, hydroxyethyliminodiacetic acid, and hydroxyethylethylenediaminetriacetic acid; and the surfactant is a combination of palmitoleic acid and polyethylene glycol.

[0228] The quartz boat after pickling is washed with water, firstly, the quartz boat after pickling is soaked in pure water, and then sprayed and rinsed;

[0229] The temperature of static soaking is 12℃, and the time of static soaking is 25min;

[0230] The temperature of the spray rinse is 15°C and the flow rate of the spray rinse is 12m 3 / h, the spray rinsing time is 30min.

[0231] The quartz boat after water washing is slowly pulled and dehydrated.

[0232] The dehydrated quartz boat is dried.

[0233] Step 2, testing the air tightness of the furnace tube;

[0234] Step 3, loading the film and placing it in the boat, heating the furnace tube and keeping the temperature constant at 640°C for 590 seconds, while nitrogen gas was introduced for 4 minutes;

[0235] Step 4: Vacuum, evacuate to bottom pressure for 3 minutes, and keep the temperature constant at 590°C;

[0236] Step 5: Constant pressure ventilation, the furnace tube pressure rises and remains constant at 570°C;

[0237] Step 6: The first high-temperature silane is introduced at 660°C, a silane flow rate of 600 sccm, and a time of 50 min; the second high-temperature silane is introduced at 620°C, a silane flow rate of 630 sccm, and a time of 35 min; and the third high-temperature silane is introduced at 600°C, a silane flow rate of 450 sccm, and a time of 38 min.

[0238] After step 7 and step 6, vacuum is applied, and the vacuuming condition is set at a temperature of 580°C and a time of 2.5 minutes;

[0239] Step 8: back pressure. The back pressure conditions are set as temperature at 575° C., nitrogen flow rate at 25000 sccm, and time at 2 min.

[0240] Step 9: Unload the silicon wafers from the boat, take them out of the quartz boat, insert them into the basket, and transfer them to the next process.

[0241] Example 5

[0242] Step 1, pre-treating the quartz boat, using an alkaline solution to perform alkaline washing on the quartz boat, firstly soaking the quartz boat in the alkaline solution, and then performing ultrasonic rinsing;

[0243] The temperature of static soaking is 30℃, and the time of static soaking is 35min;

[0244] The temperature of ultrasonic rinsing was 35°C, the frequency of ultrasonic rinsing was 35kHz, and the time of ultrasonic rinsing was 50min.

[0245] In the alkaline solution, NaOH accounts for 3.2% of the volume fraction of the mixed solution, and H2O2 accounts for 4.0% of the volume fraction of the mixed solution.

[0246] The quartz boat after the alkali washing is subjected to water washing, firstly the quartz boat after the alkali washing is soaked in pure water, and then sprayed and rinsed;

[0247] The temperature of static soaking is 16℃, and the time of static soaking is 22min;

[0248] The temperature of the spray rinse is 12°C and the flow rate of the spray rinse is 14m 3 / h, the spray rinsing time is 44min.

[0249] The quartz boat is pickled with a mixed acid solution, the quartz boat is firstly soaked in the mixed acid solution, and then ultrasonically rinsed;

[0250] The temperature of static soaking is 28℃, and the time of static soaking is 38min;

[0251] The temperature of ultrasonic rinsing was 34°C, the frequency of ultrasonic rinsing was 36 kHz, and the time of ultrasonic rinsing was 51 min.

[0252] The mixed acid solution is composed of 1.5% hydrogen chloride, 0.2% hydrogen fluoride, 0.4% oxidant, 0.1% complexing agent, 0.02% surfactant, and the balance is water. The oxidant is a combination of hydrogen peroxide, peracetic acid, and ammonium persulfate; the complexing agent is a combination of hydroxyethyliminediacetic acid and hydroxyethylethylenediaminetriacetic acid; and the surfactant is palmitoleic acid.

[0253] The quartz boat after pickling is washed with water, firstly, the quartz boat after pickling is soaked in pure water, and then sprayed and rinsed;

[0254] The temperature of static soaking is 14℃, and the time of static soaking is 30min;

[0255] The temperature of the spray rinse is 18°C ​​and the flow rate of the spray rinse is 10m 3 / h, the spray rinsing time is 40min.

[0256] The quartz boat after water washing is slowly pulled and dehydrated;

[0257] The dehydrated quartz boat is dried.

[0258] Step 2, testing the air tightness of the furnace tube;

[0259] Step 3, loading the film and placing it in the boat, raising the temperature in the furnace tube and keeping it constant at 700°C for 700s, while nitrogen gas is introduced for 5min;

[0260] Step 4: evacuate the chamber to the bottom pressure within 3 minutes, and keep the temperature constant at 600°C;

[0261] Step 5: Constant pressure ventilation, the furnace tube pressure rises and remains constant at 600°C;

[0262] Step 6: The first high-temperature silane is introduced, the temperature is set at 650°C, the silane flow rate is 650sccm, and the time is 60min; then the second high-temperature silane is introduced, the temperature is set at 500-650°C, the silane flow rate is 650sccm, and the time is 45min; finally, the third high-temperature silane is introduced, the temperature is set at 650°C, the silane flow rate is 650sccm, and the time is 40min.

[0263] After step 7 and step 6, vacuum is applied, and the vacuum application condition is set at 600°C for 3 minutes;

[0264] Step 8: back pressure. The back pressure conditions are set as temperature at 600° C., nitrogen flow rate at 30,000 sccm, and time at 3 min.

[0265] Step 9: Unload the silicon wafers from the boat, take them out of the quartz boat, insert them into the basket, and transfer them to the next process.

[0266] Table 2 Performance parameter data of Examples 1 to 5

[0267]

[0268]

[0269] The second group of experiments analyzed the performance parameters of the battery cells produced by the two processes. The cleaned boat support was the control group, and the uncleaned boat support was the experimental group. As can be seen from Table 2: The results showed that the yield of the experimental group was slightly improved compared with the control group, but in the field of industrial manufacturing, even a small efficiency improvement may bring huge economic benefits.

[0270] Due to the improvement of film thickness, the quality of the passivation layer has been improved, which effectively reduces surface recombination and improves the passivation effect of the battery. The optimization of passivation and doping effects has slightly increased the Voc (open circuit voltage) of the photovoltaic cell and improved the output power of the battery.

[0271] In summary, the application of unwashed PV panels in TOPCon process technology has significantly improved the performance of photovoltaic cells by improving film thickness uniformity, optimizing passivation and doping effects, and increasing Voc and FF. The application of this technology has injected new vitality into the development of the photovoltaic industry and provided strong support for the development of more efficient and environmentally friendly photovoltaic cells in the future.

[0272] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.

Claims

1. A method for improving the inter-sheet film thickness of TOPCON cells, characterized in that: The following steps are involved: Step 1, pre-treating the quartz boat, the object of pre-treatment does not include the quartz boat support; Step 2, testing the air tightness of the furnace tube; Step 3, loading wafers and boats, loading silicon wafers into quartz boats, transporting the quartz boats into furnace tubes, heating the furnace tubes and keeping the temperature constant at 600-700°C for 500-700s, and simultaneously purging with nitrogen for 3-5min; Step 4, evacuate the furnace tube treated in step 3, evacuate to bottom pressure for 2 to 3 minutes, and keep the temperature constant at 550 to 600°C; Step 5, constant pressure ventilation, pre-introducing a certain amount of silane into the furnace tube treated in step 4, so that the furnace tube pressure rises and maintains a constant pressure, and the temperature is constant at 550-600° C.; Step 6, multi-layer deposition process, firstly high temperature silane is introduced, and silane is thermally decomposed into a first layer of silicon element deposited on the surface of the passivation layer; The second high-temperature silane is passed, and the silane is thermally decomposed into a second layer of silicon element deposited on the surface of the passivation layer; the third high-temperature silane is passed, and the silane is thermally decomposed into a third layer of silicon element deposited on the surface of the passivation layer; Step 7: After the multi-layer deposition process is completed, the unreacted gas and some products are pumped out of the furnace tube through a vacuum pump; Step 8: Back pressure: fill the furnace tube with nitrogen to return the pressure to normal pressure, ready for boat unloading; Step 9: Unload the silicon wafers from the boat, take them out of the quartz boat, insert them into the basket, and transfer them to the next process.

2. The method for improving the inter-sheet film thickness of TOPCON cells according to claim 1, characterized in that: The pre-processing comprises the following steps: The quartz boat is treated with alkaline solution; The quartz boat after alkali washing is subjected to water washing; The quartz boat is pickled with a mixed acid solution; The quartz boat after pickling is washed with water; The quartz boat after water washing is slowly pulled and dehydrated; The dehydrated quartz boat is dried.

3. The method for improving the inter-sheet film thickness of TOPCON cells according to claim 2, characterized in that: The alkaline solution is a mixed solution of NaOH and H2O2, wherein the volume fraction of NaOH in the mixed solution is 2.5-4.0%, and the volume fraction of H2O2 in the mixed solution is 3.5-6.0%.

4. The method for improving the inter-sheet film thickness of TOPCON cells according to claim 3, characterized in that: The mixed acid solution comprises the following components by mass percentage: 0.3-1.5% of hydrogen chloride, 0.1-0.2% of hydrogen fluoride, 0.05-0.4% of oxidant, 0.05-0.1% of complexing agent, 0.02-0.05% of surfactant, and the balance is water.

5. The method for improving the inter-sheet film thickness of TOPCON cells according to claim 4, characterized in that: The oxidant is selected from any one of hydrogen peroxide, peracetic acid or ammonium persulfate, or a combination of at least two thereof; The complexing agent is any one of ethylenediaminetetraacetic acid, hydroxyethyliminodiacetic acid, and hydroxyethylethylenediaminetriacetic acid, or a combination of at least two thereof; The surfactant is any one of palmitoleic acid, polyethylene glycol or fatty alcohol polyoxyethylene ether, or a combination of at least two of them.

6. The method for improving the inter-sheet film thickness of TOPCON cells according to any one of claims 2 to 5, characterized in that: The alkali washing treatment is carried out according to the following steps: Firstly, the quartz boat is placed in the alkaline solution for soaking, and then ultrasonically rinsed; The temperature of the static soaking is 15-35°C, and the time of the static soaking is 30-50 minutes; The temperature of ultrasonic rinsing is 30-40°C, the frequency of ultrasonic rinsing is 30-40kHz, and the time of ultrasonic rinsing is 45-60min; The pickling treatment is carried out according to the following steps: Firstly, the quartz boat is placed in the mixed acid solution for static soaking, and then ultrasonically rinsed; The temperature of the static soaking is 15-35°C, and the time of the static soaking is 30-50 minutes; The temperature of ultrasonic rinsing is 30-40°C, the frequency of ultrasonic rinsing is 30-40kHz, and the time of ultrasonic rinsing is 45-60min; The specific steps of the water washing treatment are: First, place the quartz boat after acid or alkali washing in pure water for static soaking, and then spray rinse; The temperature of the static soaking is 10-20°C, and the time of the static soaking is 20-40 minutes; The temperature of the spray rinsing is 10-20°C, and the flow rate of the spray rinsing is 5-15m 3 / h, the spray rinsing time is 30 to 60 minutes.

7. The method for improving the inter-sheet film thickness of TOPCON cells according to claim 1, characterized in that: The constant pressure in step 5 was maintained at 150 mbar.

8. The method for improving the inter-sheet film thickness of TOPCON cells according to claim 1, characterized in that: The vacuuming conditions in step 7 are set at a temperature of 550-600° C. and a time of 1-3 minutes.

9. The method for improving the inter-sheet film thickness of TOPCON cells according to claim 1, characterized in that: The back pressure conditions in step 8 are set as a temperature of 550-600° C., a nitrogen flow rate of 10,000-30,000 sccm, and a time of 1-3 min.

10. The method for improving the inter-poly film thickness of TOPCON cells according to claim 1, characterized in that: The parameters of the first deposition in step 6 are set as temperature at 500-650° C., silane flow rate at 200-650 sccm, and time at 45-60 min. The parameters of the second deposition are set as temperature at 500-650° C., silane flow rate at 200-650 sccm, and time at 30-45 min. The parameters of the third deposition are set as follows: temperature is set at 500-650° C., silane flow rate is 200-650 sccm, and time is 35-40 min.

Citation Information

Patent Citations

  • Method for improving uniformity of high-temperature oxide layers of wafers

    CN101906617A

  • Wafer boat assembly and semiconductor process equipment

    CN116240527A

  • Saturation method of LPCVD (Low Pressure Chemical Vapor Deposition) quartz boat and quartz boat for Topcon battery

    CN118388147A

  • Method of manufacturing semiconductor device and substrate processing apparatus

    JP2012104719A

  • Cleaning Apparatus and Cleaning Method using the Same

    KR1020120003109A